CGIAR’s AWARE platform: promoting early warning of and effective response to climate hazards - Amarnath, Giriraj (CGIAR, 2025)
As the climate crises worsens, extreme weather events are becoming increasingly more frequent and variable. This exacerbates the risks facing people in climate-vulnerable low- and middle-income countries. The Early Warning, Early Action, Early Finance (AWARE) platform, developed by the CGIAR Research Initiative on Climate Resilience (ClimBeR) helps countries overcome such challenges and protect communities ahead of impending climate-related hazards, rather than afterwards. The platform is based on the principle of ‘early warning to early action and early finance,’ which emphasizes the importance of anticipatory action measures to mitigate the impacts of hazards and reduce human and economic losses.